Utilization of Video Media in The Use of Capital Letters In Grade 4 Students at 1 Megawon Elementary School - Velayali, Istifaiya; Tika Aniffaturrif'ah; Aulia, Syarifah Nur; Fitriyani, Vivin; Ulfa, Emilia; Susendra, M. Ari; Nuha, Rif'an Ulin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze the ability to use capital letters of grade 4 students at SD 1 Megawon by using learning videos. This research uses descriptive quantitative methods with data collection techniques using tests. The population in this study were students at SD 1 Megawon while the sample in this study were 4th grade students of SD Megawon, consisting of 17 students, The data collection technique was using a test instrument. Data were analyzed using descriptive statistics. The results showed that the average score of students' capitalization skills was 7.29 with a range of 4. Normality test shows that the data is normally distributed. The frequency distribution analysis per indicator showed that the indicators that were answered correctly the most by students were the beginning of sentences and names of people, while the indicators that were still difficult for students to master were the names of months and ethnic groups. Descriptive statistical analysis of exploration showed that the ability of female students was superior compared to male students in writing names of people, geographical names, and names of months.